Internalisasi Nilai Dari Semboyan Satu Tungku Tiga Batu Melalui Mata Kuliah Pendidikan Agama Islam Di Politeknik Negeri Fakfak - Syamsul, Muhammad Ayyub; Dessy Eka Kuliahsari (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research aims to investigate how the values ​​of the motto "Satu Tungku Tiga Batu" are understood and internalized through Islamic Education learning at Fakfak State Polytechnic. In this context, Islamic Education plays a significant role in shaping individuals' character and morality. The motto, which carries the meaning of unity, cooperation, and mutual support, has not been fully interpreted in the context of Islamic learning at Fakfak State Polytechnic. A case study method is used to examine how this motto is applied in the Islamic Education curriculum. Data were collected through participatory observation, interviews with lecturers and students, and content analysis of lecture materials. The results of this research highlight the importance of the role of Islamic education in shaping understanding and acceptance of moral values ​​among students. The implications of these findings include suggestions for curriculum development and strategies to enhance the integration of Islamic values ​​in an academic context. This research contributes to understanding how Islamic education can strengthen ethical principles and reinforce communal bonds within the educational environment.